2016
DOI: 10.1108/md-01-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of knowledge management on growth performance in construction industry

Abstract: Purpose The main purpose of this study is to examine the relationship between knowledge management and growth performance of construction companies. Design/methodology/approach Six hundred questionnaires were sent to selected individuals in grade G7 construction companies. A total of 110 completed questionnaires were returned and deemed usable. The collected data were processed and analysed by partial least-squares (PLS) path modelling wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Consistent with Saks (2006), job engagement is allied to job satisfaction, organizational commitment, and organizational citizenship behavior, and undesirably associated with intent to quit. Organizational Performance: Abu Bakar et al (2016) scrutinized the relationship between knowledge management practices and growth performance in the construction industry. Growth performance measurement assumed through company turnover and employment progress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consistent with Saks (2006), job engagement is allied to job satisfaction, organizational commitment, and organizational citizenship behavior, and undesirably associated with intent to quit. Organizational Performance: Abu Bakar et al (2016) scrutinized the relationship between knowledge management practices and growth performance in the construction industry. Growth performance measurement assumed through company turnover and employment progress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In increasingly competitive construction industry context, there are growing concerns about knowledge-based innovations (Abu Bakar et al, 2016). Simultaneously, higher education institutes have a growing interest in achieving strategic goals through improved research cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the complementing mutual interests, a profound relationship between higher education research institutions, i.e., universities, who are the developers of knowledge, and industry organisations, who are the users of knowledge, becomes significant in advancing towards achieving such novel goals (Pucciarelli and Kaplan, 2016). Yet, throughout the time, academic research in construction management is often claimed for not adequately assisting the construction industry development (Abu Bakar et al, 2016;Fairclough, 2002;Latham, 1994). This urges the need for re-defining the research roles of academia and the industry in terms of enabling construction management innovations.…”
Section: Introductionmentioning
confidence: 99%
“…Many benefits can be gained from the utilization of knowledge transfer (Abu Bakar et al, 2016). According to Osabutey and Jin (2016), firms' efficiency will improve if the supportive KM system is entrenched in their operations and functioning.…”
mentioning
confidence: 99%
“…Abu Bakar et al (2016) stated that once the management of a construction organization prioritizes the importance of knowledge transfer in achieving its set organizational goals, its workforce will consciously channel its resource towards activities that encourage good knowledge transfer practice and increased productivity. Furthermore, Khalfan et al (2010) reported that some of the benefits of the knowledge transfer in supply chain management include a community of practice, facilitating cooperation, continuous work, and future work opportunities with the same client for a longer time.…”
mentioning
confidence: 99%